2017
DOI: 10.2208/journalofjsce.5.1_422
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Real-Time River Stage Prediction Method Using Deep Learning

Abstract: The real-time river stage prediction model was developed using the artificial neural network model, with deep learning as the training method. The main component of the model was the four-layer feed-forward network. As a network training method, the stochastic gradient descent method based on the back propagation technique was applied. The denoising autoencoder was applied as a pre-training method. The developed model was applied to one catchment of the Ooyodo River, one of the first-grade rivers in Japan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…The time-series water-level predictions of A1-A4 using the CNN in Domain A showed acceptable agreement with the observed data, although the higher peaks of each of A1-A3 were poorly captured. Comparisons with other neural networks, such as the fully connected deep neural network (FCDNN) [7] and recurrent neural network (RNN) [31] indicated that our CNN prediction was poorer than the performance of these models. For example, Hitokoto and Sakuraba [7] reported that their FCDNN provided better predictions of water levels for the top-four largest flood events from 1990 to 2014 in the same watershed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The time-series water-level predictions of A1-A4 using the CNN in Domain A showed acceptable agreement with the observed data, although the higher peaks of each of A1-A3 were poorly captured. Comparisons with other neural networks, such as the fully connected deep neural network (FCDNN) [7] and recurrent neural network (RNN) [31] indicated that our CNN prediction was poorer than the performance of these models. For example, Hitokoto and Sakuraba [7] reported that their FCDNN provided better predictions of water levels for the top-four largest flood events from 1990 to 2014 in the same watershed.…”
Section: Discussionmentioning
confidence: 94%
“…Comparisons with other neural networks, such as the fully connected deep neural network (FCDNN) [7] and recurrent neural network (RNN) [31] indicated that our CNN prediction was poorer than the performance of these models. For example, Hitokoto and Sakuraba [7] reported that their FCDNN provided better predictions of water levels for the top-four largest flood events from 1990 to 2014 in the same watershed. The RMSE in an hour prediction of water level was 0.12 m, which is approximately 1/3 of the mean RMSE of our CNN prediction, due to the use of two different verification methods.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We compared the proposed forecast approach with three existing methods: The multilayer neural network, the distributed runoff model with particle filter, and the conventional local linear method. Note that the results of the multilayer neural network and the distributed runoff model are scanned values in Hitokoto et al (2017).…”
Section: Proposed Algorithm To Forecast Unprecedented River Stagesmentioning
confidence: 99%
“…The first relates to performance when considering previously unexperienced flood magnitudes. As neural network models assume black box functions and perform interpolations using past data with these functions, they may show a poor performance when using data that exceed the range of the training data (Hitokoto et al., 2017), and it is difficult to analyze the real dynamics of these data. The other issue concerns the amount of data required.…”
Section: Introductionmentioning
confidence: 99%